PENGARUH PENGENDALIAN INTERNAL, MORALITAS DAN PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD PADA LPD SE- KECAMATAN DENPASAR UTARA - Ni Made Mita Ariastuti; Rai Dwi Andayani W; Ni Putu Yeni Yuliantari (UNHI Press, 2020)
The purpose of this study was to determine the effect of internal control, morality and the implementation of good corporate governance on fraud prevention in LPDs in North Denpasar District. There are 10 LPDs in the Village Credit Institutions (LPD) throughout North Denpasar District. The number of respondents who owned as many as 40 people with the perposive sampling method. Data collection was carried out through questionnaires. The data analysis technique used is the validity and reliability test, the classic assumption test, the coefficient of determination, the model feasibility test (F test), the t test, and multiple linear regression analysis. Based on the analysis, it is known that there is an effect of internal control, morality and the implementation of good corporate governance. has a positive effect on fraud prevention. This is evidenced as follows: 1.) Internal control with a value of t = 0.001 which is smaller than Î± (real level) = 0.05, thus H1 is accepted. 2.) Morality with a t value of 0.878 below Î± = 0.05, and a tcount of -0.155, thus H2 is rejected. 3.) The implementation of Good Corporate Governance with a value of 0.914 above Î± = 0.05, and a tcount of 0.109, thus H3 is rejected.